1993
DOI: 10.1016/0735-1097(93)90423-x
|View full text |Cite
|
Sign up to set email alerts
|

Multipolar endocardial mapping of the right atrium during cardiac catheterization: description of a new technique

Abstract: This new system may ultimately assist in mapping simple or complex atrial arrhythmias during cardiac catheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Furthermore, multisite simultaneous mapping tools, such as, multielectrode BC, are now available (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multisite simultaneous mapping tools, such as, multielectrode BC, are now available (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Previous simultaneous mapping studies of the intact right atrium (RA) and the left atrium (LA) were limited to the epicardium, 12,13 whereas simultaneous multisite endocardial mapping studies were performed only in the RA. 14,15 Since the description of Bachmann's bundle as the major conduit between the atria, 16,17 little is known about other electrical connections between the RA and LA and their role in the spread of activation, particularly along the septum. Mapping the activation patterns simultaneously on the right and left aspects of the septum and on a beat-by-beat basis enables us to identify regions of electrical linkage between the atria and to better understand their role during normal and abnormal atrial rhythms, which may further improve therapy with catheter ablation or pacing.…”
mentioning
confidence: 99%
“…Jenkins et al [1] described a 25-pole BC (Cordis-Webster, Baldwin Park, CA) that was used for endocardial mapping in the right atrium during sinus rhythm and atrial tachycardia. The authors concluded that the new system fulfilled the reasonable criteria for mapping of atrial arrhythmias and prudently recommended its use in selected patients with complex arrhythmias.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Basket catheters have been used successfully in several experimental animal studies as mapping tools to define atrial [1] and ventricular arrhythmias [2,3•]. Jenkins et al [1] described a 25-pole BC (Cordis-Webster, Baldwin Park, CA) that was used for endocardial mapping in the right atrium during sinus rhythm and atrial tachycardia.…”
Section: Animal Studiesmentioning
confidence: 99%